The effect of strategic good corporate governance and human resources management on organizational performance of the Indonesian Navy Aviation Center Mediated by Organizational Culture - Imam Musani; Willy Arafah; S.Pantja Djati (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to examine the effect of strategic Good Corporate Governance and human resources on organizational performance of the Indonesian Navy Aviation Center mediated by organizational culture. The population in this study were Puspenerbal soldiers and Puspenerbal Surabaya ranks with a total sample of 314 respondents. This study uses path modeling analysis techniques with AMOS tools. From the tests conducted, it was found that Strategic Good Corporate Governance has a positive effect on organizational performance, Human resource management has a positive effect on organizational performance, Strategic Good Corporate Governance has a positive effect on organizational culture, Human resource management has a positive effect on organizational culture, Organizational Culture has a positive effect on Organizational Performance, Organizational Culture mediates the effect of Strategic Good Corporate Governance on organizational performance and Organizational Culture mediates the effect of Human Resource Management on Organizational Performance